Code-switching and Code-mixing in the Conversation between President Joko Widodo and Nadiem Makarim on the State Secretariat Youtube Channel - Rahman, Aditya; Putri, Selfi Mahat; Putri, Diantri Seprina; Henanggil, Mita Domi Fella; Sari, Hanifah Yulia (Proceeding International Conference on Malay Identity, 2023)
Code-switching and code-mixing are common phenomena in multilingual societies, such as Indonesian society. This study aims to describe the code-switching and code-mixing in the conversation between President Joko Widodo and Nadiem Makarim on the State Secretariat Youtube Channel. The study employed a qualitative research method with observation and note-taking techniques to collect data. The data was analyzed using qualitative data analysis, which includes data reduction, data presentation, and conclusion drawing. The results showed that there were code-switching and code-mixing in the conversation between President Joko Widodo and Nadiem Makarim. The code-switching in the conversation involved switching from Indonesian to Arabic, Sanskrit, and Javanese. Meanwhile, code-mixing involved the insertion of English and Arabic words into Indonesian sentences.